Implementation of Ultrasonic Sensor as a Radar for Obstacle Detection - Ahmad Suaif; Ferizandi Qauzar Gani (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2021)
The Arduino UNO, ultrasonic sensor, servo motor, and Processing as visual software was used to create a low cost ultrasonic radar system that can detect and determine the location of an object, such as obstacles, in a short distance. Objects can be sensed up to 40 cm away from the ultrasonic sensor and the ultrasonic radar's angular rotation can detect objects from 15o to 165o and counterclockwise. The obstacle objects will be displayed in the computer panel by running the visual software. A comparative analysis of the distance error between the radar and the obstacles is used to assess the feasibility of the proposed system. The findings obtained from measurements of the obstacles are tabled to show that the planned design achieved a relatively small error, with 90% as the lowest accuracy.